The role of cannabinoid system in consolidation of passive avoidance memory in the shell of nucleus accumbens in male Wistar rats - Khalil Rasekhi; Sharbanoo Oryan; Mohammad Nasehi; Mohammadreza Zarrindast (یافته‌های نوین در علوم زیستی, 2015)
There are multiple neurotransmitters and neuromodulator systems mediating memory formation among which the endocannabinoid system plays a critical role in the memory formation by modulating the release of many neurotransmitters. Nucleus accumbens appears to have a site in the central of neuronal circuits of the limbic system and to be responsible for the integration and consolidation of inputs from other parts of the brain. In this study the influence of bilateral intra-nucleus accumbens shell microinjections of cannabinoid receptor agents on memory consolidation in adult male rats using passive avoidance task was investigated. The results showed that the intra-accumbens shell microinjection of ACPA as a CB1 receptor agonist (6 ng/rat) immediately after training decreased passive avoidance memory consolidation, while administration of its antagonist (AM251) at different doses did not affect passive avoidance memory consolidation. However, co-administration of AM251 (60 ng/rat) with an effective dose of ACPA prevented the impairment memory consolidation induced by ACPA. These results suggest that the accumbens shell cannabinoid system as a modulating system is involved in aversive memory consolidation including passive avoidance memory.